РЕЗИСТИВНІ ДАТЧИКИ НА ОСНОВІ НАНОЦЕЛЮЛОЗИ ДЛЯ ВИЯВЛЕННЯ ВОЛОГОСТІ ПОВІТРЯ - LAPSHUDA, V.; KOVAL, V.; DUSHEIKO, M.; YASIIEVYCH, Yu.; BARBASH, V.; YASHCHENKO, O. (PH “Akademperiodyka”, 2024)
Introduction. The measurement of relative air humidity plays a crucial role in various aspects of human life, such as climate control systems, medical breath and skin hydration monitoring. Typically, humidity sensors use inorganic materials and petroleum-derived polymers. However, there is a growing trend towards the transition to biodegradable materials, which eliminates the need for waste disposal.Problem Statement. Currently, nanocellulose (NC) has been being explored as a promising material for humidity sensors. However, the influence of the chemical composition and nanoparticle size of NC on the sensor characteristics remains understudied.Purpose. This study aims to investigate the influence of the chemical composition and structure of NC on the parameters of humidity sensors.Materials and Methods. NC has been synthesized from reed stalks and wheat straw bz the oxidation and acid hydrolysis methods. NC-film sensors having a mass within 0.3—3 mg have been fabricated. The static parameters (response, sensitivity, reversibility, and repeatability) and the dynamic parameters (short and long-term stability, response and recovery time) of the sensors have been analyzed.Results. The manufacturing method influences the NC chemical composition, while the origin material affects its structure. The sensors produced by the oxidation method have demonstrated improved sensitivity (2.69 · 106), response (0.2 (%RH)–1), recovery time (60 s) and long-term stability (1.44%) as compared with those made by the hydrolysis method. Additionally, the application of wheat straw NC as origin material has resulted in improved reversibility (5%), repeatability (5% deviation), short-term stability (30% deviation), and response time (1 s) as compared with the reed stalks NC.Conclusions. It has been established that the origin material of nanocellulose influences the reversibility, repeatability, response time, and short-term stability of the sensors. The manufacturing method has effect on the sensitivity, response, recovery time, and long-term stability of the sensors.